Power dynamics and new directions in the recent evolution of CBNRM in Botswana. Issue 1 (10th April 2020) - Cassidy, Lin
Abstract: Recently, the limited control of Botswana's community conservation organizations, or trusts, over resources has been further eroded. Community trusts now exist solely to disburse funds allocated by central government. The absence of any rights to control access to or use of their resources suggests the complete collapse of Botswana's original community‐based natural resources management (CBNRM) model. This collapse could facilitate fresh approaches that return to the original intentions currently lost behind the CBNRM acronym. Access and control can be more clearly framed through broader environmental stewardship frameworks that include moving below the homogenized community identity to specific resource user groups; broadening the conservation focus beyond monetized wildlife to include other resources and ecosystem processes; and establishing formal conservation agreements separately for specific resources, with the trust coordinating adherence to the rights and responsibilities held by individual users on the one hand, and government or public agencies on the other.